Preliminary Microstructure and Hardness Studies of A356/Stainless Steel Composite via Gravity Die Casting Technique - Mazlee Mohd Noor; Shamsul Baharin Jamaludin, Assoc. Prof. Dr.; Kamarudin Hussin, Kol. Prof. Dato’ Dr.; Shaiful Rizam Shamsudin; K. Ismail (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.